2008
DOI: 10.2196/jmir.1108
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Determinants of Uptake and Use of an Internet Physical Activity and Weight Management Program in Office and Manufacturing Work Sites in England: Cohort Study

Abstract: Background Internet-based physical activity (PA) and weight management programs have the potential to improve employees’ health in large occupational health settings. To be successful, the program must engage a wide range of employees, especially those at risk of weight gain or ill health.Objective The aim of the study was to assess the use and nonuse (user attrition) of a Web-based and monitoring device–based PA and weight management program in a range of employees and to determine if engagement with the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 41 publications
(55 reference statements)
3
63
0
1
Order By: Relevance
“…Likewise, Hurling et al [52] used accelerometers and found that a test group who used an automated, Internet-based physical activity program along with mobile phone technology showed a 2-h, 18-min per week increase in physical activity. In their Internet-based physical activity study of workers, Ware et al [53] concluded that the use of interactive devices to measure activity and weight data was not only useful to document results objectively, but was also associated with motivating participants to use the site (the dropout rate was only 5 percent).…”
Section: Evidence From Ehealth Research On Interventions?mentioning
confidence: 99%
“…Likewise, Hurling et al [52] used accelerometers and found that a test group who used an automated, Internet-based physical activity program along with mobile phone technology showed a 2-h, 18-min per week increase in physical activity. In their Internet-based physical activity study of workers, Ware et al [53] concluded that the use of interactive devices to measure activity and weight data was not only useful to document results objectively, but was also associated with motivating participants to use the site (the dropout rate was only 5 percent).…”
Section: Evidence From Ehealth Research On Interventions?mentioning
confidence: 99%
“…Similar data were obtained by Buis et al (2009) showing a response rate of only 15% despite inviting 47,000 candidates and drop-out rates of 21% during intervention. Overall, low response rates are a common problem in other similar intervention studies (Spittaels et al, 2007b;Verheijden et al, 2007;Ware et al, 2008). This shows that even the technological possibilities and unlimited availability of the internet is not sufficient to improve self-motivation.…”
Section: Discussionmentioning
confidence: 99%
“…To account for high drop-out rates reported in similar studies (Slootmaker et al, 2009;Spittaels et al, 2007b;Verheijden et al, 2007;Ware et al, 2008), the sample size was increased by 40% (= 140 participants). Participants were randomly allocated to the two groups in a 3:2 ratio (IG:CG) in order to increase information on a structured exercise intervention (60 persons had to be allocated to the IG and 40 to the CG).…”
Section: Sample Sizementioning
confidence: 99%
“…As a result of tailoring, Internet-based programs have become applicable to various age-groups, occupations, and sexes [24,28,29]. For example, in a cohort study among 4440 participants, those above the age of 65 performed considerably better in an Internet-based weight loss program, compared to younger participants.…”
Section: Adaptationmentioning
confidence: 99%
“…In addition, they found that diverse occupational groups including office workers and factory workers were both committed to the program. Even shift workers and computer illiterate individuals accomplished the goals of the intervention program -increased their physical activity level and adopted healthier eating habits [29].…”
Section: Adaptationmentioning
confidence: 99%